Road vehicle following control strategy using model reference adaptive control method stability approach - Hassan, Aveen U. (Penerbit UTM Press, 2015)
In convoy system, the control system on each vehicle requires information about proceeding vehicle motion, in order to maintain stability and satisfy operating constraints. A two-vehicle look-ahead control strategy is proposed and investigated for the operation of a convoy. The mathematical modeling for this control strategy has been formulated and simulated in this paper. This paper demonstrates the design process of an adaptive controller gain for a road vehicle following system. This process is done by simulation. The appropriate constants are used as the reference model for the adaptive controller implementation to find the effectiveness of the control. As a result, a road vehicle following system with an adaptive gain controller is produced.